Factors influencing the requirements engineering process in offshore software development outsourcing environments. Issue 6 (16th November 2020) - Shafiq, Muhammad; Zhang, Qinghua; Azeem Akbar, Muhammad; Alsanad, Ahmad; Mahmood, Sajjad
Abstract : Offshore software development outsourcing (OSDO) is one of the popular development paradigms in the software industry. There are a number of challenges associated with OSDO including the challenges related to requirements engineering (RE) process. The objective of this study is to identify success factors (SFs) associated with RE processes in the OSDO context. A total of 25 SFs were identified using systematic literature review (SLR) and the identified SFs were further validated with practitioners using a questionnaire‐based survey. The authors also examined the identified RE challenges with respect to their relevance for different organisation types (client and vendor) and sizes (small, medium, and large) with an aim to provide a clear understanding of the RE process and its SFs in the context of various OSDO organisations. They also conducted a comparative analysis between the SLR and questionnaire findings and the results indicate that there is a moderately positive correlation between the data sets. They believe that the findings of this study will provide a comprehensive model to help OSDO organisations assess and improve the effectiveness and efficiency of their RE activities.